The early component of middle latency auditory-evoked potentials in the process of deviance detection. Issue 10 (6th July 2016) - Li, Linfeng; Gong, Qin
Abstract : The aim of the present study was to investigate both the encoding mechanism and the process of deviance detection when deviant stimuli were presented in various patterns in an environment featuring repetitive sounds. In adults with normal hearing, middle latency responses were recorded within an oddball paradigm containing complex tones or speech sounds, wherein deviant stimuli featured different change patterns. For both complex tones and speech sounds, the Na and Pa components of middle latency responses showed an increase in the mean amplitude and a reduction in latency when comparing rare deviant stimuli with repetitive standard stimuli in a stimulation block. However, deviant stimuli with a rising frequency induced signals with smaller amplitudes than other deviant stimuli. The present findings indicate that deviant stimuli with different change patterns induce differing responses in the primary auditory cortex. In addition, the Pa components of speech sounds typically feature a longer latency and similar mean amplitude compared with complex tones, which suggests that the auditory system requires more complex processing for the analysis of speech sounds before processing in the auditory cortex.